The Impact of the Global Financial Crisis on the Debt, Liquidity, Growth, and Volume of Companies in Palestine Stock Exchange - Sabri, Tamer Bahjat Hussain; Sweis, Khalid Mohammad (Journal of Social Economics Research, 2015)
This study examines the magnitude of the potential impact of the global financial crisis on the companies listed in Palestine stock exchange and its effects on the Palestinian economy. And that mainly by knowing, if the period after the crisis debt ,liquidity ,growth ,turnover ratios is not significantly differing from pre-crisis era. To achieve the objectives of the study, a sample of 23 Palestinians companies listed at Palestine stock exchange was studied. The study covered the period from the period before the global financial crisis (2006, 2007) and the period after the global financial crisis (2009, 2010). T-Tests and Mann-Whitney-U Tests were used to test the ninth hypotheses of the study. It was concluded that the impact of the global financial crisis is limited. Which means there are no differences after the financial crisis compared to the pre- financial crisis variables.